2004
DOI: 10.1007/s00221-004-1904-3
|View full text |Cite
|
Sign up to set email alerts
|

Single joint perturbation during gait: neuronal control of movement trajectory

Abstract: The aim of this study was to investigate the effect of single joint displacement on the pattern of leg muscle electromyographic (EMG) activity during locomotion. For the first time, unilateral rotational hip or knee joint displacements were applied by a driven orthotic device at three phases of swing during locomotion on a treadmill. The response pattern of bilateral leg muscle activation with respect to the timing and selection of muscles was almost identical for displacements of upper (hip joint) or lower (k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…The only observed temporal difference among subject groups was a delayed TA response in subjects with SCI (both MCSCI and MISCI) compared to ND individuals. The response latencies observed in the TA muscle of the ND subjects were consistent with those reported previously for similar perturbations (Dietz et al, 2004). The delay in TA response observed in subjects with SCI might be due to an impaired or absent input from supraspinal centers which normally function to modulate spinal neuronal responses to afferent input (Berger et al, 1984;Dietz et al, 1989).…”
Section: Autonomy Of the Spinal Cord To Generate Compensatory Responssupporting
confidence: 90%
See 2 more Smart Citations
“…The only observed temporal difference among subject groups was a delayed TA response in subjects with SCI (both MCSCI and MISCI) compared to ND individuals. The response latencies observed in the TA muscle of the ND subjects were consistent with those reported previously for similar perturbations (Dietz et al, 2004). The delay in TA response observed in subjects with SCI might be due to an impaired or absent input from supraspinal centers which normally function to modulate spinal neuronal responses to afferent input (Berger et al, 1984;Dietz et al, 1989).…”
Section: Autonomy Of the Spinal Cord To Generate Compensatory Responssupporting
confidence: 90%
“…The DGO utilized in this study greatly reduces the postural requirements normally associated with locomotion. Nevertheless, the pattern of leg muscle activation has been shown to be similar during walking within and without the DGO in ND subjects (Dietz et al, 2004). However, the reduced postural requirements might contribute to differences in the response pattern to perturbations.…”
Section: Task-dependency Of the Response Patternmentioning
confidence: 98%
See 1 more Smart Citation
“…Interlimb reflexes are known to be relevant for postural stability (Dietz 2002). For instance, during walking, bilateral leg muscle responses are elicited by unilateral rotational hip or knee joint perturbations, and these may serve to restore the physiological movement trajectory (Dietz et al 2004). Bilateral responses elicited by unilateral treadmill acceleration or deceleration or electrical stimulation of the tibial nerve appear to be specific for the type of perturbation and dependent on the phase of the gait cycle in which the perturbation occurs (Berger et al 1984).…”
mentioning
confidence: 99%
“…Alternatively, it is possible that the differences in the stability of the leg kinematics at heel-contact and mid-swing may be related to the viewpoint that stance and swing phase dynamics are governed by different balance control mechanisms (FrenkelToledo et al, 2005;Gabell and Nayak, 1984). This notion is partly supported by experimental evidence that has shown that humans respond differently to disturbances experienced in the different phases of the gait cycle (Dietz et al, 2004). However, additional studies are necessary to better understand the differences in stability of the leg kinematics during the stance and swing phase.…”
Section: Discussionmentioning
confidence: 99%